2015
DOI: 10.5053/ejobios.2015.9.0.2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of plasma membrane Na+ /H+ antiporter (SOS1) gene during salinity stress in kallar grass (Leptochloa fusca)

Abstract: Background: Leptochloa fusca is a halophyte plant which is highly tolerant to saline and sodic soils and water. Moreover, L. fusca is an attractive model plant to study the mechanism of salt tolerance mainly due to its characteristics as a typical euhalophyte, having both accumulating and excreting salt properties. Soil salinity adversely affects plant growth, development and disturbs intracellular ion homeostasis resulting cellular toxicity. The Salt Overly Sensitive 1 (SOS1) gene encodes a plasma membrane Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Ramezani et al (2013) and Kim et al, (2008) The upregulation of salt overly sensitive 1 (TaSOS1) and TaTM20 under saline condition (Ramezani et al, 2013) and TaTM20 upregulation under Cd polluted conditions (Kim et al, 2008) also showed that yeast transgenic containing TaSOS1 gene has higher salt tolerance as compared to non-transgenic ones. In addition, Taherinia et al (2015) revealed that salinization was affected SOS1 transcript level positively in kallar grass (Leptochloa fusca L.) a halophyte plant which is highly tolerant to saline and sodic soil and water. Accordingly, it can be proposed that Azospirillum species may contribute to the upregulation of TaSOS1 and TaTM20 gene expression in wheat plants under saline and Cd polluted condition and improve salinity and Cd tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Ramezani et al (2013) and Kim et al, (2008) The upregulation of salt overly sensitive 1 (TaSOS1) and TaTM20 under saline condition (Ramezani et al, 2013) and TaTM20 upregulation under Cd polluted conditions (Kim et al, 2008) also showed that yeast transgenic containing TaSOS1 gene has higher salt tolerance as compared to non-transgenic ones. In addition, Taherinia et al (2015) revealed that salinization was affected SOS1 transcript level positively in kallar grass (Leptochloa fusca L.) a halophyte plant which is highly tolerant to saline and sodic soil and water. Accordingly, it can be proposed that Azospirillum species may contribute to the upregulation of TaSOS1 and TaTM20 gene expression in wheat plants under saline and Cd polluted condition and improve salinity and Cd tolerance.…”
Section: Introductionmentioning
confidence: 99%